The academic market and the rise of universities in medieval and early modern Europe (1000-1800) - David De la Croix; Frédéric Docquier; Alice Fabre; Robert Stelter (University of Basel, Center of Business and Economics (WWZ), 2022)
We argue that market forces shaped the geographic distribution of upper-tail human capital across Europe during the Middle Ages, and contributed to bolstering universities at the dawn of the Humanistic and Scientiffc Revolutions. We build a unique database of thousands of scholars from university sources covering all of Europe, construct an index of their ability, and map the academic market in the medieval and early modern periods. We show that scholars tended to concentrate in the best universities (agglomeration), that better scholars were more sensitive to the quality of the university (positive sorting) and migrated over greater distances (positive selection). Agglomeration, selection and sorting patterns testify to an integrated academic market, made possible by the use of a common language (Latin).
Keywords: N33; O15; I25; 330; Upper-Tail Human Capital; Universities; Discrete choice model; Scholars; Publications; Agglomeration